Optimizing graphene-TiO2 interface properties via Fermi level modulation for photocatalytic degradation of volatile organic compounds. Issue 5 (1st April 2020) - Zhou, Zhen; Gao, Junxian; Zhang, Guangsheng; Dong, Yuming; Wang, Zhenyu; Li, Ji; Lyu, Jinze
Abstract: The interfacial interaction between graphene and semiconductors significantly affects volatile organic compound (VOC) adsorption and charge separation. Herein, we optimize the interaction between TiO2 and reduced graphene oxide (rGO) by reducing the Fermi level of GO with Cu 2+ . The surface photocurrent (SPC) and surface photovoltage (SPV) of the prepared materials were tested under different atmospheres to study the effect of enhanced interfacial interactions on charge separation. The results revealed that Cu 2+ treatment tended to induce the TiO2 nanoparticles to form a thicker and more uniform layer on the rGO surface. The composition of TiO2 nanoparticles and rGO generated a 2D arranged porous structure that had both hydrophobic rGO and hydrophilic TiO2 as the pore walls. The amount of adsorbed toluene for the optimized TiO2 -graphene (t-TiO2 /rGO) was 1.21-fold higher than that for TiO2 /rGO. The SPC and SPV results showed that the optimized contact between TiO2 and rGO significantly enhanced photogenerated electron mobility and toluene-induced hole utilization. Given the advantages in adsorption and charge separation, the photocatalytic reaction rates of t-TiO2 /rGO were 1.47-fold and 1.91-fold higher than those of TiO2 /rGO and porous TiO2, respectively.